2019
DOI: 10.3389/fmicb.2019.01943
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycling in Soybean Rhizosphere: Sources and Sinks of Nitrous Oxide (N2O)

Abstract: Nitrous oxide (N 2 O) is the third most important greenhouse gas after carbon dioxide and methane, and a prominent ozone-depleting substance. Agricultural soils are the primary anthropogenic source of N 2 O because of the constant increase in the use of industrial nitrogen (N) fertilizers. The soybean crop is grown on 6% of the world’s arable land, and its production is expected to increase rapidly in the future. In this review, we summarize the current knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Deriving potential N 2 O emissions solely on the basis of N inputs can lead to an underestimation of the estimated values, particularly in the case of soybean crops. In this case, the estimated potential emissions from our study are zero, while the emissions observed in situ, which depend on other factors, are not [38,39]. Then, the emission factor value and values of mineral nitrogen inputs used are subject to criticism.…”
Section: Discussionmentioning
confidence: 76%
“…Deriving potential N 2 O emissions solely on the basis of N inputs can lead to an underestimation of the estimated values, particularly in the case of soybean crops. In this case, the estimated potential emissions from our study are zero, while the emissions observed in situ, which depend on other factors, are not [38,39]. Then, the emission factor value and values of mineral nitrogen inputs used are subject to criticism.…”
Section: Discussionmentioning
confidence: 76%
“… Bradyrhizobium japonicum is found in leguminous root tips, where it ultimately stimulates soybean growth ( 1 ). The nitrogen-fixing properties of B. japonicum have made it a popular inoculant in crop production, with recent efforts to identify remedial applications ( 2 , 3 ).…”
Section: Announcementmentioning
confidence: 99%
“…The 47,808-bp DNA genome sequence of Paso has a predicted 95% coding density and a GC content of 55% compared to 64% in the host ( 1 ). PhageTerm ( 18 ) predicts the genome sequence to start with a T7-like 371-bp direct terminal repeat.…”
Section: Announcementmentioning
confidence: 99%
“…Inoculation of legumes with rhizobia has been considered as an environmental-friendly agricultural practice recommended all over the world as part of a strategy for N 2 O mitigation (Torres et al 2016). However, it has been reported that legume crops also contribute to N 2 O production by providing N-rich residues for decomposition (Baggs et al 2000;Sánchez et al 2019), or directly by some free-living or symbiotically-associated rhizobia that are able to denitrify (Bedmar et al 2005 Alfalfa (Medicago sativa L.) is one of the most valuable forage crops and the most productive forage legume in zones with temperate climate (Delgado and Lloveras 2020). This crop does not require nitrogen fertilization, since it is able to x up to 463 kg of N 2 per ha and year, which is mainly used for the synthesis of their own protein.…”
Section: Introductionmentioning
confidence: 99%